EFEKTIFITAS BIJI KELOR (Moringa oleifera LAMK) UNTUK PENANGGULANGAN BAKTERI COLI PADA AIR SUMUR - A. Latif, Ulfa Triyani (Teknosains: Media Informasi Sains dan Teknologi, 2014)
research was done about the using of morings (Moringa oleifera Lamk.) seed dusk in overcoming of coli bacteria on water well. The purpose of this research to know effectiveness of the using morings seed in water preparation. Samplewas taken from water well of lodging which contain coli bacteria that exeed from limit threshold that was >1600 cell/100 ml water. Water well is given treatment with use morings seed dusk that was measured, amount to 0,05 gram,0,1 gram, and 0,15gram. Then morings seed dusk was mixed with little water until have the shape of paste. Paste of morings seed was mixed into 200 ml water, after that water was filtered by gause material. Filtrate was gotten that mixed into 2 liters water and was stired during 15 menits, then keeped quiet during 2hours. Higyenis water was gotten that taken amount to 100 ml for evaluation as bacteriology with metode of Most Probable Number (MPN). The output after the treatment with morings seed dusk at first water well, decrease of bacteria amount limit 1,2 cell/100 ml water. The output of experiment showed that water well was processed with morings seed save to be consumed by peoples.